Comparative analysis of ESD versus EMR in a large European series of non-ampullary superficial duodenal tumors* - Enrique Pérez-Cuadrado-Robles; Lucille Quénéhervé; Walter Margos; Leila Shaza; Hrvoje Ivekovic; Tom G. Moreels; Ralph Yeung; Hubert Piessevaux; Emmanuel Coron; Anne Jouret-Mourin; Pierre H. Deprez (Endoscopy International Open, 2018)
Background and study aims The choice of endoscopic submucosal dissection (ESD) or endoscopic mucosal resection (EMR) in non-ampullary superficial duodenal tumors (NASDTs) is challenging and the benefits of ESD remain unclear. The aim was to comparatively analyze the feasibility, outcomes and safety of these techniques in these lesions. Patients and methods This is an observational and retrospective study. All consecutive patients presenting with NASDTs who underwent EMR or ESD between 2005 and 2017 were included. The following main outcomes were comparatively evaluated: en-bloc and complete (R0) resection rates, and local recurrence. Secondary outcomes were perforation and delayed bleeding. Results One hundred sixty-six tumors in 150 patients (age: 66 years, range: 31 – 83, 42.7 % males) were resected by ESD (n = 37) or EMR (n = 129) and included. The median procedure time (81 vs. 50 min, P = 0.007) and tumor size (25 vs. 20 mm, P = 0.01) were higher in the ESD group. The global malignancy rate was 50.3 %. There were no differences in en-bloc resection (29.7 % vs. 44.2 %, P = 0.115), complete resection (19.4 % vs. 35.5 %, P = 0.069), and local recurrence (14.7 % vs. 16.7 %, P = 0.788) rates. Tumor size was associated with recurrence (28 vs. 20 mm, P = 0.008), with a median follow-up of 6.5 months. Focal recurrence (n = 22, 13.3 %) was treated endoscopically in 86.4 %. En-bloc resection in the ESD group was comparable in large ( ≥ 20 mm) and small lesions (27.6 % vs. 37.5 %, P = 0.587), while this outcome decreased significantly in large lesions resected by EMR (17.4 % vs. 75 %, P < 0.001). Nine perforations were confirmed in 6 lesions (16.2 %) resected by ESD and 3 (2.3 %) by EMR (P = 0.001). Endoscopic therapy was successful in all but 1 patient (88.9 %) presenting with a delayed perforation. Conclusions ESD may be an alternative to EMR and surgery in selected NASDTs, such as large duodenal tumors where EMR achieves low en-bloc resection rates and the local recurrence may be higher. However, this technique may have a higher risk of perforations.